Foreign Direct Investment, Governance and Inclusive Growth in Sub-Saharan Africa - Isaac K. Ofori; Simplice A. Asongu (ZBW - Leibniz Information Centre for Economics, 2021)
Motivated by the projected rebound of foreign direct investment (FDI) inflow to sub-Saharan Africa (SSA) following the implementation of the AfCFTA and the finalization of the Africa Investment Protocol, we examine how FDI modulates the effects of various governance dynamics on inclusive growth in SSA. We do this by testing two hypotheses– first, whether unconditionally FDI and various governance indicators (rule of law, control of corruption, regulatory quality, governance effectiveness, political stability, and voice and accountability) foster inclusive growth in SSA; and second, whether these governance dynamics engender positive synergy with FDI on inclusive growth in SSA. Using data from the World Bank's World Governance Indicators and the World Development Indicators for the period 1990–2020, we employ several fixed effects, random effects, and the system GMM estimators for the analysis. First, we find that FDI and all our governance dynamics are significant inclusive growth enhancers in SSA. Second, though FDI amplifies the effects of all our governance dynamics on inclusive growth in SSA, governance effectiveness, voice and accountability, and political stability are keys. Policy recommendations are provided.
Keywords: F6; F15; O43; O55; R58; 330; AfCFTA; Economic Integration; FDI; Governance; Inclusive Growth; Africa